Missionaries and the Emergence of Modern Agricultural Science in China - LI Yindi, (Journal of Research for Christianity in China (JRCC), 2025)
Agriculture is the foundation of governance. Throughout history, edicts encouraging farming and reclaiming wasteland were repeatedly issued, mobilizing all human resources to maximize land productivity. When agricultural affairs were well-managed, agricultural governance was established. However, since the opening of the ports, missionaries introduced Western scholarship. Through descriptions and introductions of Western agricultural colleges, farming implements, and agricultural chemistry, modern Chinese intellectuals became aware of the concept of agronomy—that “agriculture has its own science.” Following the Qin and Han dynasties, agriculture and scholarship diverged sharply. The tradition of scholars abstaining from farming was broken, and scholars gradually gained agricultural knowledge. Subsequently, literati and gentry began organizing agricultural associations and publishing agricultural journals to promote Western agricultural methods. Under the influence of these publications and public discourse, imperial court memorials departed from the conventional emphasis solely on cultivation benefits. They began advocating emulating the West, seeking to understand soil suitability and master cultivation techniques. This ultimately swayed the imperial court, leading authorities to explicitly propose that reforming agricultural administration must first involve advancing agricultural science. Agricultural science emerged from nothingness, entered the formal education system, and was placed within the Agricultural College of the Imperial University and the Agricultural School of the Industrial College. Its emergence signaled the dawn of a new era and embodied the spirit of the times.